ASEAN’s Resilient Soft Power in Building Peace and Shaping Sustainable Development - Khang, Tran Nguyen (Journal of Ecohumanism, 2024)
Soft power is a concept introduced by Professor Joseph Nye about the ability of actors in international relations to achieve what they want through the use of attraction and persuasion instead of coercion or bribery. The term is now widely used by analysts and politicians around the world. However, most studies on soft power focus on countries, especially developed Western countries, rather than developing non-Western countries, communities, groups, international or regional organizations, which have also created positive influences in international relations in many diverse forms and ways. In the context of fierce globalization and regionalization, ASEAN is an interesting case that has created compelling successes in soft power as a cohesive community. The study will examine and evaluate the significance of ASEAN’s integration process in creating the power of attraction in the international arena, towards creating peace and sustainable development. At the same time, building the soft power of the community is also an opportunity for member countries to enhance their position and influence, with a typical example can be considered as Vietnam. Studying about ASEAN soft power will help us understand the nature of the community’s strength, in the diversity of political - cultural - economic - social conditions, thereby contributing to further understanding the nature of soft power in international relations.